Alterations in Morphology and Adult Neurogenesis in the Dentate Gyrus of Patched1 Heterozygous Mice - Antonelli, Francesca; Casciati, Arianna; Tanori, Mirella; Tanno, Barbara; Linares-Vidal, Maria V.; Serra, Noemi; Bellés, Monserrat; Pannicelli, Alessandro; Saran, Anna; Pazzaglia, Simonetta (Frontiers in Molecular Neuroscience, 2018)
Many genes controlling neuronal development also regulate adult neurogenesis. We investigated in vivo the effect of Shh signaling activation on patterning and neurogenesis of the hippocampus and behavior of Patched1 heterozygous mice (Ptch1+/-). We demonstrated for the first time, that Ptch1+/- mice exhibit morphological, cellular and molecular alterations in the dentate gyrus (DG), including elongation and reduced width of the DG as well as deregulations at multiple steps during lineage progression from neural stem cells to neurons. By using stage-specific cellular markers, we detected reduction of quiescent stem cells, newborn neurons and astrocytes and accumulation of proliferating intermediate progenitors, indicative of defects in the dynamic transition among neural stages. Phenotypic alterations in Ptch1+/- mice were accompanied by expression changes in Notch pathway downstream components and TLX nuclear receptor, as well as perturbations in inflammatory and synaptic networks and mouse behavior, pointing to complex biological interactions and highlighting cooperation between Shh and Notch signaling in the regulation of neurogenesis